2011
DOI: 10.1073/pnas.1103360108
|View full text |Cite
|
Sign up to set email alerts
|

Functional SNP in the microRNA-367 binding site in the 3′UTR of the calcium channel ryanodine receptor gene 3 ( RYR3 ) affects breast cancer risk and calcification

Abstract: We have evaluated and provided evidence that the ryanodine receptor 3 gene (RYR3), which encodes a large protein that forms a calcium channel, is important for the growth, morphology, and migration of breast cancer cells. A putative binding site for microRNA-367 (miR-367) exists in the 3′UTR of RYR3, and a genetic variant, rs1044129 A→G, is present in this binding region. We confirmed that miR-367 regulates the expression of a reporter gene driven by the RYR3 3′UTR and that the regulation was affected by the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 44 publications
5
107
0
Order By: Relevance
“…Another study in systemic lupus erythematosus showed that rs1057233 in the 3′UTR of SPI1 was associated with the elevation of SPI1 mRNA level (Hikami et al 2011). Similar results were also found in ovarian cancer (Wynendaele et al 2010) and breast cancer (Zhang et al 2011). The existence of SNPs in miRNA targeting sites may affect the binding affinity of miRNA, thus leads to alter expression of mRNA (Medina and Slack 2008).…”
Section: Discussionsupporting
confidence: 66%
“…Another study in systemic lupus erythematosus showed that rs1057233 in the 3′UTR of SPI1 was associated with the elevation of SPI1 mRNA level (Hikami et al 2011). Similar results were also found in ovarian cancer (Wynendaele et al 2010) and breast cancer (Zhang et al 2011). The existence of SNPs in miRNA targeting sites may affect the binding affinity of miRNA, thus leads to alter expression of mRNA (Medina and Slack 2008).…”
Section: Discussionsupporting
confidence: 66%
“…There is abundant evidence that miRNAs, functioning as trans-acting factors, can bind to target genes and play an important role in regulating the development, progression, and metastasis of cancers, including BC (Jazdzewski et al, 2008;Gao et al, 2009;Hollestelle et al, 2011;Zhang et al, 2011). One such miRNA, miR-122, was first recognized as a liver-specific miRNA; it is highly expressed in the liver and is associated with liver-related diseases and hepatocellular carcinoma (HCC).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of miR-367 has been found in several types of human malignant tumors, including osteosarcoma (16), glioma (17), breast (18) and esophageal cancer (19). High expression of miR-367 in most of these tumor tissues was closely related to the poor prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%